Mali : The Selingue Rehabilitation Project - Mohan, P.C. (World Bank, Washington, DC, 2012)
The main objective of this project (1996-2002), assisted by both the World Bank and the European Investment Bank, with an initial IDA credit of US$ 27.50 million, which rose to US$ 34.21 million equivalent due to exchange rate fluctuation, was to repair and rehabilitate the Selingue Hydropower plant built 26 years ago. Other objectives were: (i) maintain the electricity supply/demand balance by increasing the thermal capacity of the system and implement an energy-efficient program; (ii) improve the capacity of the Energie du Mali (EDM) to properly operate, maintain and supervise its power generation facilities; and (iii) prepare a long-term institutional framework and regulatory system for the power sector and privatize EDM.